Field pilot study of porous asphalt pavement reinforced by cured carbon fibre composite materials (CCFCMs). Issue 3 (23rd February 2022) - Zhang, Kun; Lim, Justin; Nassiri, Somayeh; Alshareedah, Othman; Li, Hui; Englund, Karl
ABSTRACT: The use of a reinforcing fibre in porous asphalt (PA) is a common practice to improve PA's homogeneity and durability. This study developed a new type of fibre-shaped reinforcement element from cured carbon fibre composite materials (CCFCMs), which were collected from the waste stream of an aerospace manufacturing process. One control PA without CCFCMs and three PAs, which are reinforced by Fine CCFCMs, Medium CCFCMs, and re-refined Medium CCFCMs, were produced in a commercial asphalt plant and placed and compacted in the field. In-place and laboratory tests were performed to determine air voids, infiltration, and mechanical properties of PA lanes and field cores, respectively. The PA reinforced by the re-refined Medium CCFCMs exhibited the highest infiltration rate and the best ductility among these four PA mixtures. The laboratory performance results indicated that both compaction and binder draindown can influence the infiltration and mechanical performance of PA. In addition, the porosity is a more reliable parameter than air voids to correlate with water infiltration rates of PA specimens. A nuclear density gauge is highly recommended to use in the PA compaction process to monitor the in-place density and assure the hydraulic performance of PA lanes.